Dušan Makavejev's Sweet Movie - Chatzidakis, Manos 1925-1994 (<<The>> Criterion Coll., 2007)
Miss Canada wins the contest of the "most virgin" Miss Monde 1984 and the prize is marriage to a milk industry tycoon along with his 50 billion dollars fortune. During their honeymoon, Miss Canada does not accept the "golden" penis of her husband, and with the help of black man Jeremiah Muscle, she runs away to Paris. There she meets a Latin singer, El Macho, they have intercourse in the Eiffel Tower and get stuck together. She moves to a weird anarchic community and later becomes an actress working in a chocolate advertisement. Meanwhile, the revolutionary, pedophile, and mad killer Anna Planeta makes candy in her boat while sailing through the canals of a city that seems to be Amsterdam. She meets the sailor Potemkin and they have a torrid affair. Meanwhile, she uses her candies to seduce young boys and kill her lovers. In the middle of the story, what seems to be footage of a Nazi doctor and a slaughter in a war with many dead bodies is presented. Makavejev's bizarre and pointedly satirical vision is totally uncompromising and filled with shocking images, looking at sex in all its complexities.
Bildformat 1.66:1, enhanced for 16:9 widescreen TVs. - New, restored high-definition digital transfer
Orig.: Kanada, Frankreich, Bundesrepublik Deutschland, 1974
Enth. new video interviews with Makavejev and Balkan film scholar Dina Iordanova ; actress Anna Prucnal sings a song from the film
Keywords: Frau; Beauty contestants -- Drama; Candy -- Drama; Men -- Sexual behavior -- Drama; Paraphilias -- Drama; Sex -- Drama; Women sailors -- Drama; Women -- Sexual behavior -- Drama; Comedy films; Feature films; Foreign films; Motion pictures, Canadian; Motion pictures, French; Motion pictures, German